A TLR2-Activating Fraction From Mycobacterium abscessus Rough Variant Demonstrates Vaccine and Diagnostic Potential - Le Moigne, Vincent; Roux, Anne-Laure; Jobart-Malfait, Aude; Blanc, Landry; Chaoui, Karima; Burlet-Schiltz, Odile; Gaillard, Jean-Louis; Canaan, Stéphane; Nigou, Jérôme; Herrmann, Jean-Louis (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium abscessus is a prevalent pathogenic mycobacterium in cystic fibrosis (CF) patients and one of the most highly drug resistant mycobacterial species to antimicrobial agents. It possesses the property to transition from a smooth (S) to a rough (R) morphotype, thereby influencing the host innate immune response. This transition from the S to the R morphotype takes place in patients with an exacerbation of the disease and a persistence of M. abscessus. We have previously shown that the exacerbation of the Toll-like receptor 2 (TLR2)-mediated inflammatory response, following this S to R transition, is essentially due to overproduction of bacilli cell envelope surface compounds, which we were able to extract by mechanical treatment and isolation by solvent partition in a fraction called interphase. Here, we set up a purification procedure guided by bioactivity to isolate a fraction from the R variant of M. abscessus cells which exhibits a high TLR2 stimulating activity, referred to as TLR2-enriched fraction (TLR2eF). As expected, TLR2eF was found to contain several lipoproteins and proteins known to be stimuli for TLR2. Vaccination with TLR2eF showed no protection toward an M. abscessus aerosol challenge, but provided mild protection in ΔF508 mice and their FVB littermates when intravenously challenged by M. abscessus. Interestingly however, antibodies against TLR2eF compounds were detected during disease in CF patients. In conclusion, we show the potential for compounds in TLR2eF as vaccine and diagnostic candidates, in order to enhance diagnosis, prevent and/or treat M. abscessus-related infections.